In Jewish Texas : a family memoir - Ely, Stanley E. (Texas Christian University Press, 1998)
Stanley Ely says that when the fiftieth or so person confronted him with a skeptical, "You mean you're Jewish, and you're from Texas?" he decided to do more than smile and say, "Yes." The result is this funny, caustic and nostalgic tale in the tradition of popular regionally and ethnically focused memoirs. -- Provided by publisher.